Children’s perceptions on nature’s contributions to people in Portuguese biosphere reserves - Sara H. Santos; Luciana Frazão; Joana Alves; Miguel Moreira; António Alves da Silva; António C. Gouveia; Helena Freitas (Ecosystems and People, 2025)
In recent years, an unprecedented urban lifestyle has led to a growing disconnect between people and nature, raising concerns about potential unexpected environmental impacts. Recognising children as future leaders and potential agents of change, we developed a didactic approach to introduce and explore children’s perceptions on the concept of Nature’s Contributions to People (NCP) derived from the 12 Portuguese Biosphere Reserves. Children’s perceptions were analysed through drawings and their associated descriptions. Prior to the drawing elicitation task, we conducted an educational activity where 517 children matched NCP categories and emblematic species cards to an illustrated ecosystem map of each biosphere reserve, to raise awareness of the natural and cultural values of the biosphere reserves where they live. Results showed that ‘endemic/emblematic species’ was the most frequently drawn theme (28.1%) and that within this theme, mammals were the most represented group (45.6%). Furthermore, we observed significant differences in the frequency of drawing themes between biosphere reserves, reflecting children’s recognition of the unique features of each territory, as well as its multifunctional dimensions. Overall, our results suggest that combining didactic NCP mapping activities with creative expression in environmental assessments effectively integrates children’s local knowledge, enriching the NCP framework. This is especially important for children who live in these protected areas and thus have an intrinsic connection to both nature and local culture.